Description of Post-Laparotomy Patients with Wound Dehiscence From 1st January 2019 – 31th December 2019 at Dr. Mohammad Hoesin General Hospital - Octiara Gisca Amilia; Hafizd Komar (Sriwijaya Journal of Surgery, 2021)
Introduction: Wound dehiscence is a postoperative condition that can occur several days after surgery and requires special intervention. Various risk factors sucah as patients-related and surgery-related may influence the incidence of wound dehiscence. A good understanding of these risk factors is necessary to prevent the complication and decrease mortality and morbidity. This study aims to see the characteristics of patients affected by abdominal laparotomy who are treated with wound dehiscence at dr. Mohammad Hoesin General Hospital Palembang. Methods: This research was a cross-sectional, restrospective descriptive study. Using secondary data from the medical records of Mohammad Hoesin Hospital, Palembang. Performed in the from January 2019 to December 2019. Samples were all patients who underwent abdominal laparotomy and diagnosed with post- operative wound dehiscence. Results: There were 26 subjects participated who met study critera. Subjects with post laparotomy wound dehiscence were mostly male (69%). The largest age distribution is 40-59 years old (61.53%), with the average age was 48 years old. The most common type of surgery was emergency surgery (73%). The most common albumin level was hypoalbuminemia (76%). Subjects without diabetes melitus were the most common (88%). Conclusion: Male patients, patients age 40-59 years old, underwent emergency operation, have low albumin level in blood and without diabetes melitus, are all the most common characteristic of patients diagnosed with post laparotomy wound dehiscence.